Optimization of ultrasound-assisted extraction of phenolic compounds from jussara (Euterpe edulis M.) and blueberry (Vaccinium myrtillus) fruits - ROCHA,Juliana de Cássia Gomes (2018)
Abstract This study was aimed at optimizing the ultrasound-assisted extraction (UAE) of phenolic compounds from jussara and blueberry fruits using the response surface methodology (RSM). UAE was found to be more efficient to extract phenolic compounds from both fruits than the conventional extraction. The optimum extraction conditions for the jussara fruits were: extraction time between 30 and 62 min for total anthocyanins and total phenolics, fruit:solvent ratio of 10% and 6% (w/v) for total anthocyanins and total phenolics, respectively. The ethanol concentration was non-significant (p> 0.05). Acidified water was found to be an extracting solvent as efficient as ethanol in the extraction of phenolic compounds from jussara fruits. The optimum extraction conditions for blueberry anthocyanins were: ethanol concentration between 20-70% vol, and fruit: solvent ratio greater than 20% (w/v) within the range studied. The extraction time was not significant (p> 0.05). For total phenolic content: the concentration of ethanol was between 40-80%, and fruit: solvent ratio greater than 20% (w/v) and extraction time over 50 minutes. It was possible to adjust the mathematical model for the coordinates a* (verde vs vermelho) and C* (color saturation) of the jussara extracts.